Mitigation of DME interference in LDACS1-based future air-to-ground (A/G) communications. Issue 1 (1st January 2018) - Muthalagu, Raja
Abstract: In this article, an algorithm for mitigating distance measuring equipment (DME) interference in L-band digital aeronautical communication system type 1 (LDACS1)-based aeronautical communication systems is presented. The LDACS1 is a broadband system based on orthogonal frequency-division multiplexing (OFDM) is the most promising candidate for the future air-to-ground (A/G) communications. LDACS1 is operating as an inlay system and limited to the 500 kHz spectral gap between the two adjacent DME channels of bandwidth 1 MHz. In this work, a decision directed noise estimation (DDNE) approach to mitigating the pulsed interference from DME for LDACS1 system is proposed. It improves the conventional blanking and clipping approach for interference mitigation, which typically distorts the entire received signal, by combining the blanked and the original signal. The proposed designs are carried out for both cases of AWGN channel and En-Route aeronautical channel. The simulation results highlight the impact of DME interference onto the LDACS1 system and show the performance improvement of the proposed method compared to conventional interference mitigation methods in terms of bit error rate (BER).